Report on Restructuring of the Planning Commission - Planning Commission (Planning Commission, 1950)
It may be noted that in the "Scope and Tasks" was included the building-up of the "ownership" and commitment so that a consensus is reached for facilitating the implementation of change in the Planning Commission. It was, therefore, necessary for ACORD to utilise participative processes, which would make it possible for a critical mass of the Planning Commission to experience a paradigm-shift and get involved in the process of "change - management" To facilitate this, ACORD utilized the most innovative and effective methodologies of involving large numbers in this process, including "Future Search" and "large Group Interactive Process" to create and sustain "ownership" for change.
Planning Commission Government of India
Planning Commission Government of India